Anatomical dilation for the coronary sinus ostium in patients with pulmonary arterial hypertension and its impact to trigger the atrioventricular reentrant tachycardia: a case control study. (14th October 2021) - Ding, L; Weng, S; Tang, M; Zhang, S
Abstract: Background: The incidence of atrioventricular reentrant tachycardia (AVNRT) in pulmonary arterial hypertension (PAH) patients is higher than the general population [1–3]. AVNRT had been reported with larger coronary sinus (CS) ostium in general population, while the mechanism and correlation between AVNRT and the CS ostium in PAH patients are poorly understood. Purpose: We aim to investigate the impact of the CS ostium on AVNRT and find out its risk factors in PAH patients. Methods: Of 102 pulmonary arterial hypertension (PAH) patients with catheter ablation of SVT, 10 patients confirmed AVNRT who underwent computed tomographic angiography (CTA) were enrolled as study group. The control group (PAH patients without SVT, n=20) were matched in a ratio of 2:1 based on gender and BMI. We measured maxium diameter of CS ostium in axial and LAO plane by CTA. All baseline characteristics and imaging materials were collected. Results: PAH patients with AVNRT were older (45.9±14.8 vs. 32.1±7.6 years, P=0.025) and more likely to have larger CS ostium in LAO plane (18.6±3.3 vs. 14.8±4.0 mm, P=0.011) than those without AVNRT. The maximal diameter of CS ostium in LAO plane was an independent predictor for AVNRT in PAH patients (Odds ratio, 1.389; 95% confidence interval, 1.003–1.923; P=0.048). The cut-off value of CS ostium in LAO plane was 14.1mm (Area under curve = 0.79, P=0.012), and the sensitivity and specificity were 90% and 55%, respectively. Conclusions: The larger CS ostium in LAO plane correlated with the higher prevalence of AVNRT in PAH patients with age. Patients with CS ostium larger than 14.1mm in LAO plane are more likely to develop AVNRT. Funding Acknowledgement: Type of funding sources: None.